Severe loss of vasopressin-immunoreactive cells in the suprachiasmatic nucleus of aging voles coincides with reduced circadian organization of running wheel activity - Van der Zee, E.A; Jansen, K; Gerkema, M.P (Brain research, 1999)
Aging leads to a decrease in circadian organization of behavior. Whether this general observation is related to the finding that in older subjects the arginine–vasopressin (AVP) system in the suprachiasmatic nucleus (SCN) has deteriorated is an unsolved question. Here we assessed circadian organization of running wheel behavior and numbers of AVP cells in the SCN of old voles ( n=12, 11.5 months of age) and compared the results with data from young voles ( n=16, 4.5 months of age). A third of the young voles, but three-quarter of the old voles lost circadian rhythmicity. Analysis of daily onset to onset periodicity of running wheel activity at the age of 5 and 10 months in individual voles revealed a significant loss of precision of circadian rhythmicity at the higher age. The number of AVP cells in the SCN of old voles decreased substantially, over 78% compared to young voles in general. AVP cell numbers, however, cannot be directly correlated with the state of rhythmicity in old voles; in one of the three circadian rhythmic old voles the SCN contained the least AVP cells. This study does not support the idea of a causal relationship between aging induced reduction in AVP cells in the SCN and the presence of circadian rhythmicity in behavior.